Elimination of Contrast Agent Gadobutrol with Sustained Low Efficiency Daily Dialysis Compared to Intermittent Hemodialysis - Hanno Bunz; Otto Tschritter; Michael Haap; Reimer Riessen; Nils Heyne; Ferruh Artunc (Karger Publishers, 2019)
Background: In patients with renal failure, gadolinium-based contrast agents (GBCA) can be removed by intermittent hemodialysis (iHD) to prevent possible toxic effects. There is no data on the efficacy of GBCA removal via sustained low efficiency daily dialysis (SLEDD) which is mainly used in intensive care unit (ICU) patients. Methods: We compared the elimination of the GBCA gadobutrol in 6 ICU patients treated with SLEDD (6-12 h, 90 L dialysate) with 7 normal ward inpatients treated with iHD (4 h, dialysate flow 500 mL/min). Both groups received 3 dialysis sessions on 3 consecutive days starting after the application of gadobutrol. Blood samples were drawn before and after each session and total dialysate, as well as urine was collected. Gadolinium (Gd) concentrations were measured using mass spectrometry and eliminated Gd was calculated from dialysate and urine. Results: The initial mean plasma Gd concentration was 385 ± 183 µM for the iHD and 270 ± 97 µM for the SLEDD group, respectively (p > 0.05). The Gd-reduction rate after the first dialysis session was 83 ± 9 and 67 ± 9% for the iHD and the SLEDD groups, respectively (p = 0.0083). The Gd-reduction rate after the second and third dialysis was 94-98 and 89-96% for the iHD and the SLEDD groups (p > 0.05). The total eliminated Gd was 89 ± 14 and 91 ± 4% of the dose in the iHD and the SLEDD groups, respectively (p > 0.05). Gd dialyzer clearance was 95 ± 22 mL/min and 79 ± 19 mL/min for iHD and SLEDD, respectively (p > 0.05). Conclusions: Gd-elimination with SLEDD is equally effective as iHD and can be safely used to remove GBCA in ICU patients.